Redefining roles: librarians as partners in information literacy education - Helene Williams; Anne Zald (Information Research: An International Electronic Journal)
UWired is a collaborative effort at the University of Washington to bring electronic communications and information technology into the service of teaching and learning. This paper addresses the role that librarians have played in transforming undergraduate courses, pedagogy, facilities design, and faculty development to bring information literacy into departmental curricula.